An efficient algorithm for mobile objects localization - Salamah, M.; Doukhnitch, E. (John Wiley & Sons Ltd, 2008)
A new efficient algorithm based on time of arrival to determine the position of a mobile object (MO) in a wireless environment is proposed. Since all operations in our algorithm are simple add and shift operations, it can be easily implemented in the MO's firmware or hardware to reduce the number of instructions and computational cost involved in the localization task. Simulation results show that the proposed algorithm outperforms other algorithms in terms of computational cost and implementation simplicity. Copyright (C) 2007 John Wiley & Sons, Ltd.
Keywords: localization; time of arrival; fast vector rotation; CORDIC